Effect of Short-term Coenzyme Q10 Supplementation and Precooling on Serum Endogenous Antioxidant Enzymes of Elite Swimmers. Issue 5 (May 2018) - Emami, Ali; Tofighi, Asghar; Asri-Rezaei, Siamak; Bazargani-Gilani, Behnaz
Abstract : Abstract: Emami, A, Tofighi, A, Asri-Rezaei, S, and Bazargani-Gilani, B. Effect of short-term coenzyme Q10 supplementation and precooling on serum endogenous antioxidant enzymes of elite swimmers. J Strength Cond Res 32(5): 1431–1439, 2018—This study aimed to investigate the effect of the use of a 2-week precooling strategy and supplementation coenzyme Q10 (CoQ10 ) on superoxide dismutase (SOD), catalase (CAT), and serum glutathione peroxidase (GPx) in elite, adolescent swimmers during heavy and regular trainings and recording of freestyle swimming. Thirty-six healthy males (mean ± SD ; age: 17.5 ± 1.1 years, body fat content: 14.55 ± 1.75%) were randomly selected and divided into 4 groups of CoQ10 (300 mg·d −1 ), precooling (immersion in the water at 18 ± 0.5° C), supplementation with precooling, and control, each with 9 participants. During an 18-session protocol in the morning and evening, participants attended speed and endurance trainings for 5 km every session. A 3-stage blood sampling was conducted before the first recording and before and after the second recording in 800, 200, and 50 m. Repeated measurement and the Bonferroni correction were used for the statistical analyses of the data (α = 0.05). According to the results, there was no significant difference between the mean serum level of SOD, CAT, and GPx in the groups at the first stage of blood sampling ( p > 0.05). At the third stage, a significant difference was observed among all groups ( p < 0.05). At the second stage, precooling and control groups show a significant increase compared with the supplementation and supplementation with precooling groups ( p < 0.05). As an antioxidant essential for adenosine triphosphate synthesis, CoQ10 supplementation prevented adverse changes of antioxidant enzymes during heavy trainings and swimming recording and decreased the serum level, while precooling individually increased serum level of antioxidant enzymes by itself.